Efforts to Increase Lecturer Involvement through Organizational Culture, Transformational Leadership and Economic Prosperity - Pratiwi, Sri Nurabdiah; Amini, Amini (JURNAL AL-TANZIM, 2023)
This study analyses efforts to increase lecturer involvement through organizational culture, transformational leadership and economic prosperity. The background of this research is located at STIT Al-Ittihadiyah Labuhanbatu Utara, North Sumatra Province. The research subjects included six lecturers, consisting of 4 permanent lecturers of the PGMI Study Program and two permanent lecturers of the PIAUD Study Program, as well as information from higher education leaders and the foundation. This study uses a qualitative approach to the type of case study. The results of this study conclude that the moral and direct involvement of private lecturers who teach at STIT Al-Ittihadiyah Labuhanbatu Utara increases from 2017 to 2022 based on 3 (three) aspects; the first is a conducive organizational culture based on integrity, professionalism and the principle of kinship. Second, the transformational leadership practised by high school leaders prioritizes the target of change rather than just a structural position. Third is economic welfare, where lecturers are given a monthly salary according to the number of teaching credits and salary allowances for permanent lecturers from the North Sumatra Al-Ittihadiyah educational foundation. The implications of this study show the importance of the role of leaders in stimulating the level of activeness of private university lecturers, so it is recommended for future researchers to analyze this variable in public universities, which have a higher level of lecturer welfare.Organizational Culture, Transformational Leadership, Lecturer Participation